Coffee Bean’ Lipids. A critical review of contemporary scientific literature - Portillo Rodríguez, Ostilio Rolando (LACCEI, 2025)
The coffee bean´s lipids are energy reserves stored in the endosperm in the form of oil bodies intended to be used for the development of the embryo during the germination process. However, due to its low concentration in relation to the seed´s dry weight, the coffee bean is not considered an important source of vegetable oil for industrial purposes. However, when the bean is subjected to supercritical extraction processes during the production of decaffeinated coffees, as well as during the instant coffee production, the oil is isolated, but it must be subjected to subsequent purification processes to separate its different fractions to use those with industrial value. This essay focuses on the study of coffee beans’ lipids (primary metabolites) before and after roasting, their influence on cup quality, biosynthesis and differences linked to the involved species, their metabolism, solubility and extraction, as well as a discussion on the analytical techniques used for its determination.